2020
DOI: 10.3390/ph13110328
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Oxidative Stress by Cannabinoids and Cannabis Extracts in Differentiated Neuronal Cells

Abstract: In this proof-of-concept study, the antioxidant activity of phytocannabinoids, namely cannabidiol (CBD) and Δ9- tetrahydrocannabinol (THC), were investigated using an in vitro system of differentiated human neuronal SY-SH5Y cells. The oxidative stress was induced by hydrogen peroxide, as reactive oxygen species (ROS). Alzheimer’s disease (AD)-like pathological conditions were mimicked in vitro by treating the differentiated neuronal cells with amyloid-β1–42 (Aβ1–42) in the presence of Cu(II). We showed that TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 75 publications
5
22
0
3
Order By: Relevance
“…As already discussed in the literature, the high antioxidative properties of Cannabis sativa could be the reason for the protection of healthy cells from the cytotoxic effect of various chemotherapeutics. The same effect could also counterbalance the extracts' antiproliferative effects on healthy cells as observed in this study [62,63].…”
Section: Discussionsupporting
confidence: 57%
“…As already discussed in the literature, the high antioxidative properties of Cannabis sativa could be the reason for the protection of healthy cells from the cytotoxic effect of various chemotherapeutics. The same effect could also counterbalance the extracts' antiproliferative effects on healthy cells as observed in this study [62,63].…”
Section: Discussionsupporting
confidence: 57%
“…Importantly, THC has been reported to induce oxidative stress, an effect associated with decreased antioxidant parameters [ 69 ]. However, CBD was found to produce antioxidant effect in neuronal cells [ 70 , 71 ]. Notably, exposure to C. sativa for 30 days resulted in a reduction in the total antioxidant capacity, an effect associated with an increase in the levels reactive oxygen species in male albino rats [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strong antioxidant effects of THC have demonstrated in previous study (Hampson et al, 2000, Raja et al, 2020. Hampson et al demonstrated that this cannabinoid can be considered more potent protective compounds than tocopherol and ascorbate (Hampson et al, 2000).…”
Section: Discussionmentioning
confidence: 90%
“…Hemp or cannabis sativa L. (C. sativa L.) is one of the oldest known medicinal plants for recreational and medicinal applications by human for over thousands of years (Raja et al, 2020). This plant contains more than 500 natural compounds including bers, metabolites, proteins and oils, of which, more than 200 are metabolites including phytocannabinoids, alkaloids and avonoids and terpenoids (Brenneisen, 2007).…”
Section: Introductionmentioning
confidence: 99%